The Price of Animal’s Soul: Late-Stage Capitalism, Animal Welfare and the Law - Yogar, Hanna Nur Afifah (Universitas Muhammadiyah Yogyakarta, 2021)
The current epoch of capitalism creates more distinct issues, and one of its conflicts is the class struggle of animal workers. This paper will begin by inquiring how much is the price of an animal's soul?—and further, it will situate the Indonesian laws in the effort to accommodate the animal's protection and their welfare. The features of late-stage capitalism indicate the conflict of class struggle for animal workers. The assessment is more than an economic perspective, but human and non-human animal intra-action nexus, legal standpoint, and socio-cultural point of views. This analysis will refer to late-stage capitalism theory, Indonesian laws and other related regulations concerning animal protection, and comparative cases of animal welfare cases in Indonesia and Thailand. This paper is expected to provide an overview of the role of law in providing an understanding of animals as sentient beings rather than property.